Narrating Violation: Harriet Prescott Spofford’s “Circumstance” - Rita Bode (European Journal of American Studies)
The several critical interpretations of Harriet Prescott Spofford’s short story, “Circumstance,” generally acknowledge the presence of sexual violation, but they also tend to de-center it, either glossing over it, or enlisting the nature and implications of the assault to serve other ends. In contrast, “Narrating Violation” sees the story’s sexual assault as its main subject; it explores the methods that Spofford employs to present the sexual violation and the implications for reading “Circumstance” as a rape narrative. Spofford’s multiple ways of speaking the violation at the heart of “Circumstance” align with Emily Dickinson’s treatment of rape. The possibility that Dickinson recognized in “Circumstance” a story of rape and wrote her own poetic version of it begins to identify a literary stream in nineteenth-century American women’s writing that resists the elision of violence against women and tells of rape in a way acceptable for its time.